CERITA PENDEK “KOTA EMAS” KARYA ISHAK SAMUEL KIJNE SEBAGAI MEDIA PEMBELAJARAN KONTEKSTUAL DI PAPUA - Rumainum, Merry Ch. (JURNAL TRITON PENDIDIKAN, 2017)
This article aims to describe the use of the Golden City Short Story of Isaac Samuel Kijne as a learning medium that plays an active role in helping improve the ability of students to get to know the natural surroundings as well as the positive habits that are characteristic of regionalism. In addition, this article also helps as a learning medium close to the students in facilitating the learning process. The facts prove that the Golden City Short Story of Isaac Samuel Kijne as a contextual based learning media Papua contains five principles of feasibility as a medium of learning, namely: (1) Medium suitability with basic competencies to be achieved in the learning process, (2) Ease in aligning content (3) Medium suitability with selected learning strategy, (4) Medium compatibility with students’ learning environment, and (5) Medium utilization to enhance experience, likes, interests, individual abilities, and learning styles of students. In addition, this article also supported by all opinion from the respondents about the feasibility of the Golden City Short Story as a contextual learning medium.